Influential Factors in the Selection of Subspecialty Fellowship Training Among Surgical Trainees in Oman - Ghassan Al Habsi; Ahmed Al Ghaithi; Yousef Al Weshahi; Ahmed Jahwari (Oman Medical Journal, 2024)
Objectives: Surgical training has evolved over the past few decades, with an increasing number of surgeons pursuing subspecialty training through fellowship programs across various surgical specialties. While published reports confirm this trend, few studies explored the factors that determine which fellowship training surgical residents would pursue. This cross-sectional study aims to investigate the factors influencing fellowship choices made by surgical trainees in Oman. Methods: An online questionnaire, developed based on previously validated instruments, included 14 factors considered crucial for choosing a future career. Statistical analysis was performed to determine item-level validity, scale-level validity, and reliability. The survey was distributed via email and closed after six weeks for data analysis. Results: The survey achieved a response rate of 60.9%. The analysis revealed that the most influential factor among surveyed surgeons in selecting a subspecialty was prestige, with an average score of 2.7. The least reported influential factors were variety of cases (average score of 1.8) and personal interest (average score of 1.4). Only 57.7% of respondents received career choice guidance. Conclusions: Factors influencing the choice of surgical subspecialties vary among the different groups. This information can be valuable in designing programs and structuring professional career guidance and counseling.